Multisensory integration augmenting motor processes among older adults - Zou, Zhi; Zhao, Benxuan; Ting, Kin-hung; Wong, Clive; Hou, Xiaohui; Chan, Chetwyn C. H. (Frontiers in Aging Neuroscience, 2023)
Objective: Multisensory integration enhances sensory processing in older adults. This study aimed to investigate how the sensory enhancement would modulate the motor related process in healthy older adults.Method: Thirty-one older adults (12 males, mean age 67.7 years) and 29 younger adults as controls (16 males, mean age 24.9 years) participated in this study. Participants were asked to discriminate spatial information embedded in the unisensory (visual or audial) and multisensory (audiovisual) conditions. The responses made by the movements of the left and right wrists corresponding to the spatial information were registered with specially designed pads. The electroencephalogram (EEG) marker was the event-related super-additive P2 in the frontal-central region, the stimulus-locked lateralized readiness potentials (s-LRP) and response-locked lateralized readiness potentials (r-LRP).Results: Older participants showed significantly faster and more accurate responses than controls in the multisensory condition than in the unisensory conditions. Both groups had significantly less negative-going s-LRP amplitudes elicited at the central sites in the between-condition contrasts. However, only the older group showed significantly less negative-going, centrally distributed r-LRP amplitudes. More importantly, only the r-LRP amplitude in the audiovisual condition significantly predicted behavioral performance. This is a provisional file, not the final typeset article Conclusion: Audiovisual integration enhances reaction time, which associates with modulated motor related processes among the older participants. The super-additive effects modulate both the motor preparation and generation processes. Interestingly, only the modulated motor generation process contributes to faster reaction time. As such effects were observed in older but not younger participants, multisensory integration likely augments motor functions in those with age-related neurodegeneration.